Comprehensive study of the dollar cost averaging strategy using Python - Jiam, Tzi Yu (Nanyang Technological University, 2024)
Investing is a familiar concept for adults seeking to grow their wealth. While there are numerous strategies discussed in the finance world, Dollar Cost Averaging (DCA) stands out for its ability to instill discipline and mitigate the temptation to time the market, which often leads to suboptimal performance. Despite its widespread use, there appears to be a lack of comprehensive research and depth regarding DCA. This project investigates the effectiveness of DCA as a long-term investment strategy. The primary purpose is to analyze the potential benefits and limitations of DCA in wealth accumulation. Historical stock data from Yahoo Finance is utilized for analysis, with Python programming employed to develop a user interface for data visualization and analysis. The results indicate that DCA can be an effective strategy for wealth building over the long term, particularly when considering factors such as investment duration, frequency, and fee structures. However, it is essential to recognize the limitations and potential biases associated with DCA, including reliance on historical data and the impact of market dynamics.